Numerical Analysis of Auto-ignition of Ethanol - Raghavan, Vasudevan (International Journal of Integrated Engineering, 2011)
Renewable and alternative fuels such as ethanol find application in several combustion devices. Fundamental characteristics of these fuels in terms of ignition and burning rate are to be understood in order to use them in these applications. In this study, a numerical analysis of auto ignition characteristics of ethanol is presented. Opposed flow configuration, in which fuel and nitrogen emerges from the bottom duct and hot air flows down from the top duct, has been employed. Commercial CFD software FLUENT is used in the simulations. Global single step mechanism is used to model kinetics. For various mass fractions of fuel, the air temperature at which auto-ignition occurs has been recorded. The numerical results are compared with the experimental data available in literature.